2021
DOI: 10.1007/s00428-021-03032-6
|View full text |Cite
|
Sign up to set email alerts
|

Undifferentiated large cell/rhabdoid carcinoma presenting in the intestines of patients with concurrent or recent non-small cell lung cancer (NSCLC): clinicopathologic and molecular analysis of 14 cases indicates an unusual pattern of dedifferentiated metastases

Abstract: Undifferentiated carcinoma metastatic to the bowel is uncommon in surgical pathology practice and might be confused with primary gastrointestinal carcinoma, melanoma, lymphoma, and others. We present 14 cases of uni- (n = 9) or multifocal (n = 5) undifferentiated large cell/rhabdoid carcinoma presenting in the bowel of patients with concurrent (n = 9) or recent (diagnosed 1 to 25 months earlier; median, 4) non-small cell lung cancer (NSCLC). Patients were 6 females and 8 males, aged 52 to 85 years. Primary NSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…NSCLC with this phenotype usually exhibits a morphology of adenocarcinoma or squamous cell carcinoma 19. However, a subset of SMARCA2-deficient NSCLC was designated as undifferentiated carcinoma with variably rhabdoid cells in previous studies 21. Some may be classified as undifferentiated/sarcomatoid tumors rather than carcinoma based on the diagnostic criteria of this study.…”
Section: Discussionmentioning
confidence: 78%
“…NSCLC with this phenotype usually exhibits a morphology of adenocarcinoma or squamous cell carcinoma 19. However, a subset of SMARCA2-deficient NSCLC was designated as undifferentiated carcinoma with variably rhabdoid cells in previous studies 21. Some may be classified as undifferentiated/sarcomatoid tumors rather than carcinoma based on the diagnostic criteria of this study.…”
Section: Discussionmentioning
confidence: 78%
“…No histological type seems more conducive to the occurrence of digestive metastasis, however, different autopsy studies have shown that squamous cell carcinoma is the most common with a rate of 33%, followed by large cell (20 to 29%), and small cell lung cancer [13 to 23%) [5,8]. Yet, other more recent papers have observed that poorly differentiated pulmonary adenocarcinomas and large cell undifferentiated carcinomas seem to have a particular predilection for the GI tract [9].…”
Section: Discussionmentioning
confidence: 99%
“…A relatively new type of thoracic cancer, in particular lung cancer, with a poor prognosis has been identified to have mutations in SMARCA4 [250][251][252][253][254][255][256][257][258]. These mutations have been found in about 5% to 10% of NSCLC patients, mostly NS-NSCLC patients [259].…”
Section: Smarca4 Mutationsmentioning
confidence: 99%
“…Mutations in SMARCA4 constitute a family of mutations present in the SWI/SNF complex, in which other mutations exist, including mutations in SMARCA2 [271]. Morphological and phenotypical characteristics can point sometimes to such mutations, since these cancers can contain rhabdoid cells or even poorly differentiated cells associated with islets of epidermoid cells [250,251]. One of the key diagnostic elements is the absence of expression in the majority of cases of TTF1 on tumor cells [250,251].…”
Section: Smarca4 Mutationsmentioning
confidence: 99%
See 1 more Smart Citation